MO843PREVALENCE AND MANAGEMENT OF HYPERTENSION IN HEMODIALYSIS PATIENTS. (29th May 2021) - AlSahow, Ali; Alyousef, Anas; Alhelal, Bassam; AlRajab, Heba; Bahbahani, Yousif; Nawar, Hani; Ibrahim, Mostafa Mohammed Elsayed Mohammed; Elabbadi, Mohamed; Kamel, Vivian F; Abdallah, Emad; Kumar, Rajeev; AlSahu, Ebrahim
Abstract: Background and Aims: Hypertension (HTN) is common in hemodialysis (HD) patients & diagnosed by pre-dialysis BP >140/90 mmHg. Causes include high salt intake, volume overload, & loss of residual kidney function. Therapy includes achieving correct dry weight with each session, restricting interdialytic sodium & fluid intake & medications. We review its prevalence, factors associated with it & its management in our patients. Method: Demographics, HD prescription & medications data collected for patients from 5 dialysis centers. Results: A total of 1585 files reviewed. Males were 51.8% & mean age was 59. Mean age significantly higher for females (61 vs 57). ESKD cause was DM in 51% & HTN in 35%. However, of files reviewed, adequate data on comorbidities in 1390 patients (table 1 ), 69% had DM, 92% had HTN, 47% had CVD & 31% had BMI > 25 (which was significantly more frequent in females). HTN was more likely in older patients, diabetics & females with odds of HTN in females nearly twice the odds of HTN in males & odds of HTN with DM is 2.27 times odds of HTN without DM & one-year increase in age would increase odds of HTN by nearly 4%. Mean pre-HD BP for those with HTN was 143/76 mmHg & for those without HTN was 136/75 mmHg. HD frequency was thrice weekly in 94% & HD duration was > 3.5 hours in only 77% of patients. HDF used in 81.5%. Mean interdialytic weight gain (IDWG) was 2.8 kg, with no difference according to gender or presence of DM or HTN (Table 2 ). Higher IDWG associated with age < 65, Calcium bath of 1.75 & Sodium bath > 138 with 0.638 kg higher IDWG with calcium of 1.75 compared to calcium of 1.25. Higher IDWG was associated with higher BP. Mean volume of fluid removed per session was 2.74, which was less than mean IDWG, with no difference according to gender or DM, however, it was higher in the higher dialysate sodium group, & lower in the shorter session group (with trend towards statistical significance). CCB used to treat HTN in 62% followed by βB in 52%. Number of patients with HTN on 1 drug 21%, 2 drugs 27%, 3 drugs 23%, ≥ 4 drugs 20% & 9% missing data. Number of antihypertensives did not correlate with IDWG. Conclusion: Interdialytic weight gain in our HD patients is excessive & contributing to HTN. Patients must restrict salt & fluid intake & dialysis centers must regularly & frequently assess dry weight, ensure thrice weekly schedule & 4 hours per session are met, so excess fluid is completely removed. Also, high sodium & high calcium baths need to be avoided.